Watershed prioritization for soil conservation measures using USPED model in Nagwan Watershed - CHOUDHARY, SAKET; JAISWAL, R. K.; NEMA, A. K.; THAKUR, ARADHANA; GANGWAR, ANSHU (Journal of Soil and Water Conservation, 2020)
Soil is a backbone for human livelihoods and plant growth. In present scenarios, soil erosion becoming a worldwide environmental calamity for impends the natural environment, agriculture, and aquatic life. Consequently, it’s very important to evaluate the erosion quantity and prepare the map of the erosionprone area for sustainable planning and management of watershed based on soil conservation practices. In the present study, soil loss for Nagwan watershed was quantified using Unit Stream Power-based Erosion Deposition (USPED) model which is based on Revised Universal Soil Loss Equation (RUSLE). The GIS-based dataset consists of various thematic layers of RUSLE factors such as rainfall erosivity (R), soil erodibility (K), topographic factor (LS), crop management factor (C), and support practice factor (P) have been formulated by using GIS (Geographic Information System) software i.e. ILWIS. The thematic layers of considered factors are integrated into a GIS environment which helps to evaluate the soil loss. According to USPED model, approximately 8.26%, 28.42%, 23.51% and 15.6% of the basin area has very low, low, moderate, high risk and very high erosion risks, respectively. It was found that out of 42 subwatersheds, 11 sub-watersheds comes under very high, 7 under high, 7 under moderate and rest under low and very low priority. The study emphasized the prioritization of smaller scale hydrological units’ i.e. micro-watersheds is an ideally recommended unit to commence the soil and water conservation practices. Outcomes of the analysis suggested that the USPED model is an effective tool to quantify soil erosion and deposition for the watershed.